Study on Structural Health Monitoring (SHM) applications - Chee, Kevin Ming Feng (2013)
Load is identified as a harmful parameter to any structural components when its limits are exceeded. The ability to identify and monitor load along with its related parameters (i.e. bending stress, tensile stress etc.) is important in many engineering industries, especially the aerospace, civil and mechanical (ACM) industries. If the existing load acting on a structure goes undetected and begins to increase in magnitude, it might result in structural failure.